Involvement of ZEB1 and Snail1 in excessive production of extracellular matrix in Fuchs endothelial corneal dystrophy - Okumura, Naoki; Minamiyama, Ryuki; Ho, Leona T. Y.; Kay, Eunduck P.; Kawasaki, Satoshi; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Young, Robert D.; Quantock, Andrew J.; Kinoshita, Shigeru; Koizumi, Noriko (Laboratory Investigation, 2015)
Fuchs endothelial corneal dystrophy (FECD) due to corneal endothelial cell degeneration is a major cause of corneal transplantation. It is characterized by abnormal deposition of extracellular matrix (ECM), such as corneal guttae, accompanied by a loss of endothelial cells. Although recent studies have revealed several genomic factors, the molecular pathophysiology of FECD has not yet been revealed. In this study, we establish a cellular in vitro model by using immortalized corneal endothelial cells obtained from late-onset FECD and control patients and examined the involvement of epithelial mesenchymal transition (EMT) on excessive ECM production. We demonstrate that the EMT-inducing genes ZEB1 and SNAI1 were highly expressed in corneal endothelial cells in FECD and were involved in excessive production of ECM proteins, such as type I collagen and fibronectin through the transforming growth factor (TGF)-? signaling pathway. Furthermore, we found that SB431542, a specific inhibitor of TGF-? type I ALK receptors, suppressed the expression of ZEB1 and Snail1 followed by reduced production of ECM. These findings suggest that increased expression levels of ZEB1 and Snail1 in FECD cells were responsible for an increased responsiveness to TGF-? present in the aqueous humor and excessive production of ECM. In addition, these results suggest that the regulation of EMT-related genes by blocking the TGF-? signaling pathway may be a feasible therapeutic strategy for FECD.
EVALuna2:21239